2017
DOI: 10.5812/aapm.57102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Magnesium Sulfate and Tramadol as an Adjuvant to Intravenous Regional Anesthesia for Upper Extremity Surgeries

Abstract: BackgroundIntravenous Regional Anesthesia (IVRA) is a simple efficient method for providing regional anesthesia of the limbs. However, it has some limitations such as lack of postoperative analgesia.ObjectivesThis study aimed to compare the analgesic effects of magnesium sulfate and tramadol when added to lidocaine used for IVRA in upper limb surgery.MethodsIn this double - blind randomized clinical trial, 69 patients who underwent elective upper limb surgery with IVRA were randomly allocated into 3 groups. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…'s study comparing magnesium sulfate and tramadol as adjuvants in IV regional anesthesia for upper extremity surgery suggested that tramadol helps reduce opioid consumption and pain. [ 23 ] The results derived from the present study support their finding. In addition, Dubey et al .…”
Section: Discussionsupporting
confidence: 89%
“…'s study comparing magnesium sulfate and tramadol as adjuvants in IV regional anesthesia for upper extremity surgery suggested that tramadol helps reduce opioid consumption and pain. [ 23 ] The results derived from the present study support their finding. In addition, Dubey et al .…”
Section: Discussionsupporting
confidence: 89%
“…Tramadol is a synthetic opioid analgesic with a moderate potency whose effects vary depending on the type of opioid-specific receptors and can cause differences in the physiological parameters obtained (15). Administration of tramadol as an adjuvant for pain management or adding it to local anesthetics in various methods has enhanced their analgesic potency without increasing the incidence of adverse effects (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%